How do you solve using gaussian elimination or gauss-jordan elimination, 2x+4y-6z=482x+4y6z=48, x+2y+3z=-6x+2y+3z=6, 3x-4y+4z=-233x4y+4z=23?

1 Answer
May 19, 2017

Using Gauss elimination gives x=3x=3, y=3y=3, and z=-5z=5

Explanation:

Step 1. Rewrite the equations in matrix form
((2,4,-6,|,48),(1,2,3,|,-6),(3,-4,4,|,-23))

Step 2. Switch R_2 with R_1
((1,2,3,|,-6),(2,4,-6,|,48),(3,-4,4,|,-23))

Step 3. -2R_1+R_2->R_2
((1,2,3,|,-6),(0,0,-12,|,60),(3,-4,4,|,-23))

Step 4. -3R_1+R_3->R_3
((1,2,3,|,-6),(0,0,-12,|,60),(0,-10,-5,|,-5))

Step 5. Switch R_2 with R_3
((1,2,3,|,-6),(0,-10,-5,|,-5),(0,0,-12,|,60))

Step 6. -1/10R_2 -> R_2
((1,2,3,|,-6),(0,1,1/2,|,1/2),(0,0,-12,|,60))

Step 7. -1/12R_3->R_3
((1,2,3,|,-6),(0,1,1/2,|,1/2),(0,0,1,|,-5))

Translating back into the values x, y, and z
z=-5
y+1/2(-5)=1/2=>y=3
x+2(3)+3(-5)=-6=>x=3